\(\left(-7\right)^x=\frac{1}{49}\)
\(\Leftrightarrow\left(-7\right)^{-2}=\left(-7\right)^{-2}\)
\(\Rightarrow x=-2\)
\(\left(-7\right)^x=\frac{1}{49}\)
\(\Leftrightarrow\left(-7\right)^{-2}=\left(-7\right)^{-2}\)
\(\Rightarrow x=-2\)
tim xEz biet:
a)\(x^2+\left(y-\frac{1}{4}\right)^4=6\)
b)\(x+\left(\frac{-31}{12}\right)^2=\left(\frac{49}{12}\right)^2-x=y^2\)
c)\(\left(x-7\right)^{x+1}-\left(x-7\right)^{x+11}=0\)
\(\left(-7\right)^x=\frac{1}{49}\)
\(\left(-2\right)^x=-0,125\)
Tìm x:
\(\left(1^2+2^2+...+49^2\right)\left(2-x\right)=-1\frac{1}{5}\)
tìm x nguyên biết
a) \(\frac{1}{1.3}+\frac{1}{3.5}+\frac{1}{5.7}+...+\frac{1}{\left(2x-1\right)\left(2x+1\right)}=\frac{49}{99}\)
a,\(\left|x+\frac{1}{2}\right|+\left|x+\frac{1}{3}\right|+\left|x+\frac{1}{6}\right|=4x\)
b,\(\frac{7}{\left(x+3\right)\left(x+10\right)}+\frac{11}{\left(x+10\right)\left(x+21\right)}+\frac{13}{\left(x+21\right)\left(x+34\right)}=\frac{x}{\left(x+3\right)\left(x+34\right)}\)
Tìm x,y
a)\(\left(\frac{2}{3}:x+\frac{1}{4}\right)^2=\frac{49}{64}\)
b)\(\frac{2}{5}:\)/x-2/-1/3=1/2
c)\(\frac{1}{8}-\left(\frac{1}{12}-\frac{1}{3}x\right)^3=0\)
Tìm x biết:
a,\(\left(5x+1\right)^2=\frac{36}{49}\)
b,\(\left(2x-\frac{1}{2}\right)^2=\frac{1}{4}\)
\(x+\left(-\frac{31}{12}\right)^2=\left(-\frac{49}{12}\right)^2-x=y^2\)
Tìm x và y , Giúp tớ nha .
tìm x:
a,\(\left(x-\frac{7}{9}\right)^3=\left(\frac{2}{3}\right)^6\)
b,\(\left(\frac{x}{2}-5\right)^5=-32\)
c,\(\left(x-7\right)^{x+1}-\left(x-7\right)^{x+11}=0\)